(untitled) (Research, Society and Development, 2024)
This article provides a comprehensive review of the intersection of beyond 5G and Smart Grids, focusing on the potential of Vehicle-to-Fog as an industrial alternative for addressing energy efficiency challenges in data processing. This study aims to investigate relevant publications and patents to understand the collaborative potential between 5G and Smart Grids. It explores establishing new regulatory standards within the 5G framework to facilitate decentralized data processing and remodel energy consumption patterns. The hypothesis suggests that decentralized 5G architecture and Smart Grids can be most effectively applied through Vehicular Fog powered by solar energy. A combined quantitative and qualitative methodology guides the exploration of publications and patents. The study concludes by advocating for new standards that embrace decentralized 5G data processing, emphasizing the potential of Vehicle-to-Fog and the future deployment of 6G technology in Smart Grids. These advancements can significantly enhance energy efficiency in the context of 5G and pave the way for future innovations.